Piracy and competition - Paul Belleflamme; Pierre M. Picard (Center for Economic Studies and ifo Institute (CESifo), 2004)
The effects of (private, small-scale) piracy on the pricing behavior of producers of information goods are studied within a unified model of vertical differentiation. Although information goods are assumed to be perfectly horizontally differentiated, demands are interdependent because the copying technology exhibits increasing returns to scale. We characterize the Bertrand-Nash equilibria in a duopoly. Comparing equilibrium prices to the prices set by a multiproduct monopolist, we show that competition drives prices up and reduces total surplus.
Keywords: L13; L86; L82; K11; O34; 330; information goods; piracy; copyright; pricing; Digitale Güter; Produktpiraterie; Computerkriminalität; Betriebliche Preispolitik; Produktdifferenzierung; Duopol; Wettbewerb; Theorie